(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Annatatsiya:Ushbu maqolada O’zbekiston Respublikasining Pedagogika oliy ta’limlarida bugungi kunda tahsil olayotgan bo’lajak boshlang’ich ta’lim o’qituvchilariga “Boshlang’ich ta’limda tarbiya” fani tashkil etilgan.Ushbu faning konsepsiyasi davlatning ta’lim-tarbiya sohasidagi siyosatini amalga oshirishda mavjud bo’lgan dolzarb muammolarni hal etishga yo’naltiriladi. Konsepsiya yosh avlod tarbiyasidagi ishlarni yangi bosqichga olib chiqishga qaratilgan ustuvor vazifalar, asosiy maqsad va yo’nalishlarni belgilab beradi Abstract:This article examines the introduction and significance of the subject “Upbringing in Primary Education” in pedagogical higher education institutions of the Republic of Uzbekistan, aimed at training future primary school teachers. The study highlights that the conceptual framework of this subject is designed to address pressing challenges in the implementation of state policy in the field of education and upbringing. Particular attention is given to the integration of innovative approaches and modern pedagogical technologies in the educational process. The concept outlines priority tasks, key objectives, and strategic directions focused on enhancing the effectiveness of educating the younger generation and elevating the system of upbringing to a qualitatively new level. Аннотация:В данной статье анализируется внедрение и значение дисциплины «Воспитание в начальном образовании» в педагогических высших учебных заведениях Республики Узбекистан, направленной на подготовку будущих учителей начального образования. Подчеркивается, что концептуальная основа данной дисциплины ориентирована на решение актуальных проблем реализации государственной политики в сфере образования и воспитания. Особое внимание уделяется интеграции инновационных подходов и современных педагогических технологий в образовательный процесс. Концепция определяет приоритетные задачи, ключевые цели и стратегические направления, направленные на повышение эффективности воспитания подрастающего поколения и вывод системы воспитания на качественно новый уровень.